Evidence of IQ-Modulated Association Between ZNF804A Gene Polymorphism and Cognitive Function in Schizophrenia Patients - Chen, Min; Xu, Zhansheng; Zhai, Jinguo; Bao, Xin; Zhang, Qiumei; Gu, Huang; Shen, Qiuge; Cheng, Lina; Chen, Xiongying; Wang, Keqin; Deng, Xiaoxiang; Ji, Feng; et al. (Neuropsychopharmacology (New York, N.Y.), 2012)
ZNF804A gene polymorphism rs1344706 has been suggested as the most compelling case of a candidate gene for schizophrenia by a genome-wide association study and several replication studies. The current study of 570 schizophrenia patients and 448 controls again found significantly different genotype frequencies of rs1344706 between patients and controls. More important, we found that this association was modulated by IQ, with a stronger association among individuals with relatively high IQ, which replicated results of Walters et al, 2010. We further examined whether this IQ-modulated association also existed between the SNP and the intermediate phenotypes (working memory and executive functions) of schizophrenia. Data were available from an N-back task (366 patients and 414 controls) and the attention network task (361 patients and 416 controls). We found that the SNP and IQ had significant interaction effects on the intermediate phenotypes for patients, but not for controls. The disease risk allele was associated with poorer cognitive function in patients with high IQ, but better cognitive function in patients with low IQ. Together, these results indicated that IQ may modulate the role of rs1344706 in the etiology of both schizophrenia and its cognitive impairments, and pointed to the necessity of considering general cognitive function as indexed by IQ in the future studies of genetic bases of schizophrenia.